Investigations: The Expanded Field of Writing in the Works of Robert Morris - Katia Schneller, Noura Wedell (dir.) (ENS Éditions, 2015)
Yes, you seem to have been anything but an iconophile in your enterprise which is piled as high with words on one side as with images on the other. Robert Morris, "Professional Rules" By investigating the prolific oeuvre of Robert Morris via the prism of writing, this collection of essays provides an incisive lens into the work of a central figure in the visual arts since the 1960s, associated in turn with minimalism, postminimalism, conceptualism, and land art. Morris has often been labele...